Transformation of Da’wah Communication Patterns of Religious Advisors of Persatuan Islam - Garnita, Anggit; Zanah, Mu'minatul (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2025)
The objectives in discussing the transformation of da'wah communication patterns of religious advisors of Persatuan Islam are: first, Persis as a da'wah organization is interesting to study when there is a shift in the methods or messages of da'wah being conveyed. Second, what factors underlie the shift in da'wah among Persis religious advisors. Third, how is the process of da'wah transformation among Persis religious advisors. It is portrayed using Everett M. Rogers' diffusion of innovation theory which includes the construction of innovation, the use of communication channels, the innovation decision process, and the social system related to goal achievement. This research aims to describe the construction of the transformation of Persis preachers' communication patterns according to the understanding and experience of Persis preachers themselves. This research is a qualitative study using the phenomenological method. By using this method, it is expected to be able to present a complete picture of the transformation of communication patterns of religious advisors of Persatuan Islam. Data collection techniques are through observation and in-depth interviews. Based on the research that has been conducted, it can be concluded that there has been a transformation in the communication patterns of religious advisors of Persatuan Islam, including the material dimension. Previously, the da'wah of Persatuan Islam religious advisors was oriented toward fiqh studies, but over time there has been a transformation of da'wah material, adjusted to developing issues. The transformation of religious advisors also occurred in the rhetorical dimension. If previously the approach was agitative, rigid and polemical, then in the era of globalization, Persatuan Islam religious advisors in their da'wah activities use adaptive and persuasive communication approaches.